Research on the Protection Predicament and Digital Breakthrough Path of Rural Architecture in Shandong - Liu Qiang; Shi Nan (E3S Web of Conferences, 2021)
Rural arechitecture, as an important carrier of rural areas, faces the huge impact of modern life style and construction mode, and there is a crisis of cognitive degradation and loss of skills. with the continuous promotion of rural revitalization, the crisis of its protection and inheritance is increasingly serious, and the disadvantages of the single inheritance mode of oral transmission and personal transmission and personal transmission are also gradually revealed. In this predicament, how to innovate the inheritance of traditional skills has become an urgent problem to be solved. In the era when digital technology has penetrated into every field of modern life and become a technology booster, this paper intends to use digital technology and take the construction technology of rural architecture in Shandong province as the entry point to solve the dilemma faced by rural architecture and study the effective way of its digital inheritance and development.